The Ideologization of Al-Ghazali’s Sufi Exegesis: A Critical Analysis through Gadamer’s Philosophical Hermeneutics - Siti Nur Azizah (Al-Qudwah, 2026)
This article seeks to examine the ideological dimensions and interests embedded within Al-Ghazali’s interpretation of the Qur’an through the lens of Hans-Georg Gadamer’s philosophical hermeneutics. Its significance lies in addressing the often-adversarial positioning of hermeneutic debates in Qur’anic studies vis-à-vis classical tafsir methodologies, which tend to create a dichotomy between traditional and modern approaches. Moreover, there exists a lacuna in scholarship concerning the influence of subjectivity, ideology, and historical context on Qur’anic interpretation in classical works, particularly within Al-Ghazali’s thought. Employing a qualitative methodology, this research utilises descriptive-analytical and critical-comparative approaches. The data are analysed through Gadamer’s philosophical hermeneutics, which foregrounds historicity, prejudice, and the interpreter’s subjectivity in the process of textual understanding. The findings indicate that Al-Ghazali applied the method of illumination to apprehend the objective meaning of God’s message. Nonetheless, his interpretation also incorporates ideological elements that delimit the text to specific meanings, endorse his own group, and position others as objects within the interpretative discourse. Furthermore, the study suggests that hermeneutics should not be regarded as a threat to the authority of classical tafsir; rather, it may serve as a reflective instrument for recognising the dimensions of historicity, subjectivity, and social context in interpretation. The contribution of this research lies in its endeavour to establish a dialogical perspective between hermeneutics and classical tafsir, thereby situating debates on hermeneutics within the framework of open, critical, and proportionate academic ijtihad, as opposed to a logic of exclusivism or mutual negation.